Capturing the Developmental Changes in Cognitive Control Engagement in Chinese Preschoolers - Xufeng Ji; Yihao Deng; Qiong Zhang; Yanlin Zhou (Behavioral Sciences)
Young children typically engage in cognitive control reactively in response to specific situations, rather than proactively preparing for them. The developmental change from reactive to proactive control seems to happen gradually across early development and ultimately results in a qualitatively different behavior pattern. However, existing evidence is mainly based on cross-sectional designs. Thus, this study adopted a longitudinal design to examine the transition from reactive control to proactive control in preschoolers. Sixty preschoolers aged 4 (n = 31) and 5 (n = 29) were recruited and required to complete two cognitive control tasks (i.e., an AX-Continuous Performance Test and a Cued Task-Switching task) twice within a five-month interval. The results showed that the children improved their cognitive control skills across both tasks, demonstrating a predominantly reactive control pattern during the time interval. This improvement reflects an age-related gradual change, which is a preparation for evolving into a qualitatively different behavioral pattern over time. These findings provide longitudinal evidence for the developmental change from reactive to proactive control in early childhood strategies.